Relación entre comunicación y cambio organizacional en trabajadores de una empresa del sector terciario (2013)
The objective of this research was to determine the relationship of the communication process in the implementation of organizational change of a company in Bogota. The research was conducted under a cross-sectional and correlational design, through the application of organizational communication measuring instruments (BCC) and the measuring instrument of organizational change (BMI). 50 employees of a company in Bogota were the participants. A significant correlation was revealed between: the variables and sources of empirical knowledge of the organization; timely information and knowledge of the organization; leadership and timely information;ideal communication channels and culture change. This shows there is a relationship between organizational communication and organizational change.Keywords: organizational change, organizational communication, acceptance of change.